Advances in magnetic noble metal/iron-based oxide hybrid nanoparticles as biomedical devices - Sanchez, Laura Mabel (2019)
The study of the noble metal magnetic hybrid nanoparticles is a really promising topic from both the scientific and the technological points of views, with applications in several fields. Iron oxide materials which are hybridized with noble metal nanoparticles (NPs) have attracted increasing interest among researchers because of their cooperative effects on combined magnetic, electronic, photonic, and catalytic activities. This review article contains a summary of magnetic noble metal/iron oxide nanoparticle systems potentially useful in practical biomedical applications. Among the applications, engineered devices for both medical diagnosis and treatments were considered. The preparation to produce different structures, as blends or core-shell structures, of several nanometric systems was also considered. Several characterization techniques available to describe the structure, morphology and different kinds of properties of hybrid nanoparticles are also included in this review.